Promosi Desa Wisata Penglipuran melalui Pendekatan Digitalisasi Pada Masa Pandemi: Sebuah Studi Literatur - I Nengah Sandi Artha Putra; I Made Gede Darma Susila; Ida Bagus Gowinda Putra Udiana (Sekolah Tinggi Pariwisata Sahid Surakarta, 2022)
Penglipuran Village has historically been developed into a tourist village because it has different unique potential compared to other villages. This tourist village has won several awards as the best and most sustainable tourism village by several well-known media in the tourism sector. As a result of the impact of the covid-19 pandemic, there has been a decline in the number of tourist visits and it is necessary to take serious action for the village manager to maintain the sustainability of this tourist village. This study aims to determine the efforts made by the village managers during the pandemic by promoting based on the digitalization approach. This study uses a qualitative method with data collection techniques in the form of observation and a literature study which will be analyzed using QDA Miner Lite software. This study indicates that one of the causes that allow tourist villages to have difficulty competing with new tourist attractions in the era of digital transformation is the scenario of using and utilizing digital technology. The role of technology at this time is very important, especially as digital promotional media. This opportunity needs to be utilized by village managers to attract tourists to travel back after the pandemic, such as fostering tourist interest in traveling using virtual tours to promote tourism in Penglipuran Village.